Features extraction based on fuzzy clustering and segmentation onto the motion region for medium field surveillance application - Maliki, Mohamad Nansah (IEEE, 2004)
Fuzzy-based clustering algorithm is becoming popular in image processing, especially in image segmentation. Based on the degree of the membership function, each pixel can be grouped into â€œnatural groupâ€? of pixels according to the spatial coordinate using their values. In this work we present features extraction based on fuzzy clustering and segmentation onto the motion region for medium field surveillance application. Instead of using blob analysis, we believe that fuzzy based clustering algorithm, can also be used to generate different clusters. Incorporating the motion-based segmentation the complexity of the fuzzy clustering will also be reduced because only the motion region will be processed to the clustering algorithm.